To catch an heiress - Quinn, Julia (Piatkus Books, 2008)
When Caroline Trent is kidnapped by Blake Ravenscroft, she doesn't even try to elude this dangerously handsome agent of the crown. After all, she's been running from unwanted marriage proposals. Yes, Blake believes she's a notorious spy named Carlotta De Leon, but for six weeks until her twenty-first birthday, when she'll gain control of her fortune, hiding out in the titillating company of a mysterious captor is awfully convenient - and maybe just a little romantic, too. Blake Ravenscroft's mission is to bring 'Carlotta' to justice, not to fall in love. His heart has been hardened by years of intrigue, but this little temptress proves oddly disarming and thoroughly kissable. And suddenly the unthinkable becomes possible - and this mismatched couple might be destined for love.